The Impact of Credit Information Sharing Reforms on Firm Financing? - Martinez Peria, Maria Soledad; Singh, Sandeep (World Bank Group, Washington, DC, 2014)
This paper analyzes the impact of introducing credit information-sharing systems on firms' access to finance. The analysis uses multi-year, firm-level surveys for 63 countries covering more than 75,000 firms over the period 2002-13. The results reveal that credit bureau reforms, but not credit registry reforms, have a significant and robust effect on firm financing. After the introduction of a credit bureau, the likelihood that a firm has access to finance increases, interest rates drop, maturity lengthens, and the share of working capital financed by banks increases. The effects of credit bureau reforms are more pronounced the greater the coverage of the credit bureau and the scope and accessibility of the credit information-sharing scheme. Credit bureau reforms also have a greater impact on firms' access to finance in countries where contract enforcement is weaker. Finally, there is some evidence that the effects of credit bureau reform are more pronounced for smaller, less experienced, and more opaque firms.